Microstructure and high temperature oxidation of modified ductile Ni-resist alloy with higher manganese content - M.M., Rashidi; M.H., Idris; Z., Shayfull; A.H., Ahmad; M.M.A., Abdullah; Pietrusiewicz, P.; Nabiałek, M.; Garus, J. (Polska Akademia Nauk, 2022)
In this study, ductile Ni-resist with a minimum of 18 wt% nickel composition was modified. Up to 12 wt% manganese was added together with 10 wt% nickel to investigate the effects of the alloying elements on its microstructure, mechanical properties and isothermal oxidation behaviour. The results show a higher manganese composition on modified ductile Ni-resist with increased carbide formation, and a slightly decreased elevated temperature tensile strength. The addition of higher Mn [wt%] slightly increased the oxidation resistance. Three different oxide layers were observed on the modified ductile Ni-resist after 25 h hot corrosion at 765◦C.